Antibacterial Activity of Jotang Flower Infusion (Acmella paniculata) against Staphylococcus aureus - Skania, Pratiwi Cahya; Kholifah, Eva; Agustin, Siti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Among its various uses, the plant Jotang (Acmella paniculata), which is a member of the Asteraceae family, possesses antibacterial and anti-infective properties in its floral section. The majority of diseases are caused by the Streptococcus aureus bacteria. The purpose of this study was to evaluate the antibacterial activity of jotang flower infusion against Streptococcus mutans at doses of 75%, 50%, and 25%. The antibacterial activity was evaluated using the agar diffusion method, with chloramphenicol acting as a positive control. At 25%, 50%, and 75% dosages, the average inhibition zone diameter in the jotang inhibition test was 5.00 mm, 6.00 mm, and 6.06 mm, respectively. Chloramphenicol, the positive control, had a measurement of 9.96 mm. According to the study's results, jotang flower infusion has a somewhat effective antibacterial effect on Streptococcus aureus.